2022
DOI: 10.3389/fphar.2022.916653
|View full text |Cite
|
Sign up to set email alerts
|

The Putative Role of Astaxanthin in Neuroinflammation Modulation: Mechanisms and Therapeutic Potential

Abstract: Neuroinflammation is a protective mechanism against insults from exogenous pathogens and endogenous cellular debris and is essential for reestablishing homeostasis in the brain. However, excessive prolonged neuroinflammation inevitably leads to lesions and disease. The use of natural compounds targeting pathways involved in neuroinflammation remains a promising strategy for treating different neurological and neurodegenerative diseases. Astaxanthin, a natural xanthophyll carotenoid, is a well known antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 257 publications
(246 reference statements)
1
7
0
Order By: Relevance
“…AST also attenuated the CVD markers, i.e., extravasation (BBB damage and systemic leakage of Evans blue dye) and increased nitrite levels. These data indicate that AST regulates BBB integrity, similar to other experimental data [ 23 ]. Neuroinflammation in AD indicates the accumulation of beta-amyloid protein expression in experimental diabetic animals due to metabolic abnormalities in neuronal astrocyte function [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…AST also attenuated the CVD markers, i.e., extravasation (BBB damage and systemic leakage of Evans blue dye) and increased nitrite levels. These data indicate that AST regulates BBB integrity, similar to other experimental data [ 23 ]. Neuroinflammation in AD indicates the accumulation of beta-amyloid protein expression in experimental diabetic animals due to metabolic abnormalities in neuronal astrocyte function [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, AST is attenuated in middle cerebral-artery-occlusion-associated cerebral infarction via the inhibition of cyclic-adenosine-monophosphate-associated protein kinase A activation in mice brains [ 22 ]. Hence, AST plays a putative role in the management of neuroinflammation and has significant therapeutic potential for CVD and neurodegenerative disorders [ 23 ]. In addition, the molecular modeling study of AST is predicted to undergo non-covalent binding to matrix metalloproteinase-13 (MMP-13) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, long-term exposure of light to eyes may induce and increase ROS level, which can activate cellular pathways associated with inflammation. It has been demonstrated that astaxanthin can cross the blood-brain barrier and accumulate in the retina of animals [ 141 ]. Therefore, the consumption of astaxanthin can help maintain eye health by reducing oxidative inflammation and asthenopia by improving retinal blood flow.…”
Section: Anti-oxidative Properties Of Astaxanthin Versus Other Carote...mentioning
confidence: 99%
“…Phycocyanin when supplied to rats suffering from autoimmune disease encephalomyelitis caused downregulation of IFN-γ and IL-6 expressions (Cervantes-Llanos et al 2018 ) and many cyanobacterias and microalgal species including Spirulina platensis are enriched with phyacocyanin (Pinto et al 2022 ). Astaxanthin produced from Haematococcus inhibited production of nitrous oxide and prostaglandin E2, decreased the levels of proinflammatory cytokines (TNF-α, IL-1β, and IL-6), improved phagocytes function, diminished lipids and proteins’ oxidative damage and reduced NF-κB expression (Speranza et al 2012 ; Mularczyk et al 2020 ; Wang and Qi 2022 ). When given in dosage of 100 mg/kg and 10 mg/kg it inhibited the lipopolysaccharides’ induced inflammation and effect was comparable to prednisolone (anti-inflammatory drug) as reported by Ohgami et al ( 2003 ).…”
Section: Microalgal Bioactive Compounds and Their Potential Biologica...mentioning
confidence: 99%